2017
DOI: 10.18632/oncotarget.17629
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of inhibition of PI3K/Akt/mTOR signal pathway on chronic neuropathic pain and spinal microglia in a rat model of chronic constriction injury

Abstract: ObjectiveTo explore the effects of inhibition of PI3K/Akt/mTOR signal pathway on chronic neuropathic pain (CNP) and spinal microglia in a rat model of chronic constriction injury (CCI).MethodsMale SD rats were assigned into control, sham, CCI, wortmannin, dimethyl sulfoxide (DMSO) and wortmannin-positive control groups. Paw withdrawal mechanical threshold (PWMT) and thermal withdrawal latency (TWL) were recorded. qRT-PCR and Western blotting were used to detect PI3K, Akt and mTOR expressions and their phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…The activated P2X 4 R causes the phosphorylation of p38-MAPK, and the release of BDNF, all of which are essential to the persistence of pain hypersensitivity after nerve injury. Mounting evidence suggests that P2X 4 R may regulate the progress of neuropathic pain through the p38MAPK, ERK1/2, and PI3K/Akt pathways, which were core pathways in the development of neuropathic pain [11,[40][41][42]. Meanwhile, miR-106b could promote cervical cancer progression by modulating the expression of the GSK3B, VEGFA, and PTK2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…The activated P2X 4 R causes the phosphorylation of p38-MAPK, and the release of BDNF, all of which are essential to the persistence of pain hypersensitivity after nerve injury. Mounting evidence suggests that P2X 4 R may regulate the progress of neuropathic pain through the p38MAPK, ERK1/2, and PI3K/Akt pathways, which were core pathways in the development of neuropathic pain [11,[40][41][42]. Meanwhile, miR-106b could promote cervical cancer progression by modulating the expression of the GSK3B, VEGFA, and PTK2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of RNA gene expression of peripheral blood leukocytes from patients with chronic masticatory myalgia demonstrated that the MAPK signaling pathway was upregulated 23. PI3K-AKT-mTOR signaling pathway is involved in the activation of microglia cells and progression of chronic nerve pain 24. BDNF, synthesized in the primary sensory neurons, is anterogradely transported to the central terminals of the primary afferents in the spinal dorsal horn, where it is involved in the modulation of painful stimuli 25.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of chronic pain through mTOR inhibition is a newly studied application target for chronic pain control [16,36]. Previous studies have observed changes in chronic pain through the inhibition of mTOR signaling in the spinal cord [37][38][39][40], and recent studies have demonstrated effective modulation of chronic pain by direct mTOR signaling control in the brain [16,41], The activation of mTOR regulates protein synthesis by phosphorylating downstream effectors, which in uence a wide range of physiological and pathological states including neuropathic, in ammatory, and cancer-related pain [16][17][18], The Torin1 and XL388 used in this study were ATP-competitive inhibitors that suppress the phosphorylation of downstream effectors to regulate mRNA translation and protein synthesis [42].…”
Section: How Can Mtor Inhibition Reduce Brain Activities Of Chronic Pmentioning
confidence: 99%